Geometric morphometrics sheds new light on the identification and domestication status of 'new glume wheat' at Neolithic Çatalhöyük. (June 2022) - Roushannafas, Tina; Bogaard, Amy; Charles, Michael
Abstract: 'New glume wheat' (NGW) is an archaeobotanical type increasingly recognised at Neolithic–Bronze Age sites across Europe and Western Asia. NGW has been recognised via aDNA and morphological analyses of chaff remains as a member of the Triticum timopheevii wheat group, recent cultivation of which is known only from western Georgia. This study combines geometric morphometric (GMM) analysis of NGW grains with updated results from a parallel study of chaff dehiscence, to assess the taxonomic classification and domestication status of NGW from the Neolithic East Mound at Çatalhöyük (central Anatolia). Results confirm close comparability of NGW with modern wheats from the group T. timopheevii, in a form which has remained remarkably similar over thousands of years. Furthermore, the analysis suggests that NGW was undergoing selection for domestication traits in terms of shattering behaviour and grain form during the 1150-year East Mound sequence. These findings are interpreted in the context of substantial archaeobotanical evidence for a broad-spectrum plant strategy at Çatalhöyük which mitigated the risk of resource failure and supported experimentation in cropping. Possible cultural and practical incentives are considered for investment in the crop, made despite the availability of a fully-domesticated glume wheat (emmer) with similar growing and processing requirements. Alongside this, the study demonstrates the sensitivity of GMM to differences between and within wheat species, with methodological findings that can inform future studies. Highlights: Geometric morphometrics can identify charred archaeological wheat grains to species. Morphometrics reinforces link between archaeological remains and Timopheev's wheats. Within glume wheat species, grain shape can be linked to domestication status. Timopheev's wheat underwent selection for domestication traits at Çatalhöyük.